Hubungan Dukungan Keluarga dan Efikasi Diri dengan Kepatuhan Minum Obat Anti Tuberkulosis (OAT) pada Pasien TB Paru di Puskesmas Kabupaten Situbondo - Rahman, Handono Fatkhur; Widad, Sofil; Sholehah, Baitus (Universitas Nurul Jadid, 2024)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs and leading to significant health challenges. In 2021, 450,000 cases of multidrug-resistant tuberculosis (MDR-TB) were reported, marking a 3.1% increase from the previous year. Family support plays a vital role in motivating patients to adhere to treatment regimens, while high self-efficacy boosts patients' confidence in completing therapy. Adherence to tuberculosis treatment is defined as completing a six-month course of therapy without interruptions. This study aimed to analyze the relationship between family support, self-efficacy, and adherence to anti-tuberculosis medication (OAT) among pulmonary TB patients in Situbondo District. A cross-sectional design was employed, involving 112 respondents selected through Slovin's formula from a population of 156 TB patients at Besuki and Panji Health Centers. Data collection utilized validated questionnaires on family support, self-efficacy, and medication adherence, analyzed using the Spearman test. Results revealed a significant relationship between family support and adherence (p=0.000; r=0.443) and between self-efficacy and adherence (p=0.000; r=0.537). The study concludes that both family support and self-efficacy are crucial factors influencing adherence to tuberculosis treatment among pulmonary TB patients in Situbondo.